Analisis Penerapan Sistem Informasi Manajemen Rumah Sakit Menggunakan Metode HOT-Fit Di Rumah Sakit Universitas Sebelas Maret - Anggraini Luthfiyyah Syarry Handoko; Frestiany Regina Putri; Wahyu Ratri Sukmaningsih (LPPM POLBITRADA, 2026)
The implementation of the Hospital Management Information System (SIMRS) is an important part of supporting fast, accurate, and integrated health services. Sebelas Maret University Hospital has implemented the Techno Medic application to support Electronic Medical Records (EMR) in outpatient services. This study aims to determine the implementation of SIMRS based on the HOT-Fit approach, which includes Human, Organization, Technology, and Benefit aspects. The study used a qualitative descriptive method with data collection techniques such as in-depth interviews, observation, and documentation. Research informants consisted of outpatient registration officers, heads of medical records, and IT staff. The results showed that users were able to operate the system quite well despite having never received formal training from the vendor. The system learning process was carried out independently through manuals and assistance from colleagues. Organizational support has been provided through the provision of supporting facilities, but there is no specific SOP regarding the use of SIMRS Techno Medic. From a technological aspect, the system is considered easy to use and has features that assist services, but still encountered obstacles such as network disruptions and errors in the BPJS bridging process. From a benefits aspect, SIMRS helps speed up services, facilitates patient data retrieval, and reduces data input errors. Based on the research results, it can be concluded that the implementation of the Techno Medic SIMRS at UNS Hospital has been quite successful. However, further training, the development of specific SOPs, and periodic system development are still needed. Keywords: SIMRS, HOT-Fit, electronic medical records, hospital services, Techno Medic.